EFFECT OF ENVIRONMENTAL DEGRADATION ON ANIMAL DIVERSITY IN BALI, INDONESSIA - Kasa, I Wayan (Metamorfosa: Journal of Biological Sciences; Vol 2 No 2 (2015), 2015)
Bali is a small beautiful tropical island of Indonesia archipelago, lies between the continent of Asia and Australia, as well as the Indian and Pacific Ocean. As a tropical archipelago, many kinds of biodiversity can be found. The island of Bali in particular, there are typical animal diversity that could not be investigated beyond such island, such as, Bali cattle, Bali dog, Bali starling and others. As time goes on, the existance of such biodiversity decreases in both body weight and population number. Both global warming/climate change and land use change are the main factors affecting such phenomenon. This study has been conducted by employing field observation as well as literature study. It was found that, the quality of purebred Bali cattle species decreases genetically that could be notified of smaller bodysize for both male and female. Land use change of agriculture activity to the hotels, house of living, roads and other infrastructures are the main factors for Bali cattle existence. For typical famous bird of Balistarling, the problem is because of deforestation which cause natural habitat loss, due to land use change for agricultural activity and house building by local people. In case of Bali dog, the mad dog of rabies is just introduce and spreading over Bali island, whichis formerly the island of Bali has been recognised as free zone area of the rabies. As consequence, suffering dogs must be eliminated by  mass killing cause decrease total number of such poor dog. Overall, it could be concluded that environmental degradations of land use change, deforestation and desease are the main causes of biodiversity decreasing number of the Bali cattle, Bali white starling and Bali dog respectively, beside global warming/climate change natural disaster. Key words: Environment, Bali cattle, Bali starling, Bali dog, Bali island.
Keywords: Environment, Bali cattle, Bali starling, Bali dog, Bali island